THE ROLE OF INCOME IN THE PSYCHOSOCIAL HEALTH OF INDIVIDUALS EXPERIENCING POVERTY - Jóni Ledo; Iara Teixeira; Madalena Cruz; Inês Catarina Batista; António Oliveira; Felipe Alckmin-Carvalho; Henrique Pereira; Catarina Oliveira (LIFE: International Journal of Health and Life-Sciences, 2026)
Objective: Evaluate associations between social discrimination, self-stigma, social support and affect in a sample of Portuguese people living in poverty and analyze possible differences in these psychosocial variables between poor and very poor individuals. Method: This is a cross-sectional study involving 357 individuals aged between 18 and 70 (M =34.51; DV =14.59). The instruments used were Paradox of Self-Stigma, Multidimensional Scale of Perceived Social Support, Portuguese Everyday Discrimination Scale and Reduced Version of the Portuguese Positive and Negative Affect Scale. Results: The overall analysis revealed medium levels of social discrimination and negative affect, as well as high levels of self-stigma, perceived social support, and positive affect. Compared to the low-income group, the very low-income group reported more social discrimination and self-stigma, and lower perceived social support and positive affect. Negative affect perceived social support and salary predicted positive affect, while age, schooling, household, social discrimination and positive affect. Conclusions: Poverty was positively associated with social discrimination and self-stigma, and level of social support was a moderating variable in this association. Compared to low-income individuals, participants with very low income experienced significantly more social discrimination, self-stigma, and negative affect, suggesting a cumulative vulnerability effect of poverty on these indicators. Implementing public policies to include these populations is fundamental to combating vulnerability and reducing the adversities faced by people in situations of social vulnerability in Portugal.